Integration of computational fluid dynamics into a fluid mechanics curriculum. Issue 1 (28th March 2011) - Adair, D.; Jaeger, M.
Abstract The development, implementation and evaluation of a suitable curriculum for students to use computational fluid dynamics as part of a fluid mechanics course at intermediate undergraduate level are described. Evaluation of successful learning outcomes is made to confirm the effectiveness of the interface as a suitable educational tool for students at intermediate undergraduate level. © 2011 Wiley Periodicals, Inc. Comput Appl Eng Educ 22: 131–141, 2014